Faith-based organizations and veteran reintegration : enriching the web of support - Werber, Laura; Derose, Kathryn Pitkin, 1963-; Rudnick, Mollie; Harrell, Margaret C.; Naranjo, Diana (Research report (Rand Corporation), 2015)
Faith-based organizations (FBOs) are an important community-based resource for veterans as they readjust to civilian life. Through interviews with both national-level and smaller, local FBOs, the authors sought to understand better the current and potential roles for FBOs in veteran reintegration. Interviewees suggested that veterans may look to FBOs for support because they offer privacy and confidentiality, two features that may be especially critical when a potential stigma is involved. Some FBOs have also developed a reputation as safe places for veterans, providing supportive, judgment-free environments. FBOs not only help veterans with spiritual matters but address diverse areas of veteran health and wellness, including vocation, education, financial and legal stability, shelter, access to goods and services, mental health, access to health care, physical health, family, and social networks. In some cases, the support is offered to veterans directly; in other instances, the support is indirect, via training individuals to help veterans or educating the public about them. In the process of providing support, FBOs interact with varied organizations, including government entities, private nonprofits, and one another, for training, outreach, referrals, information exchange, obtaining donations, and collaboration. Yet challenges exist, including insufficient connections with chaplains working in different settings and others in the web of support, resource and capacity constraints, lack of awareness of experience with veterans, issues related to religious philosophy or orientation, and characteristics of veterans themselves. To move forward, the authors offer recommendations for policymakers, organizations that interact with FBOs, and FBOs themselves to help FBOs engage fully in the web of reintegration support.